CAPTISOL® AS CHIRAL SELECTOR IN CAPILLARY ELECTROPHORESIS OF NON-ACIDIC DRUGS - Monica Budău; Gabriel Hancu; Zoltán István Szabó; Hajnal Kelemen; Aura Rusu; Daniela Lucia Muntean; Anca Gabriela Cârje (Journal of the Chilean Chemical Society, 2017)
Enantioseparation of nine extensively used chiral pharmaceutical substances from different pharmacological classes and with different structural characteristics has been investigated by capillary zone electrophoresis using Captisol® (sulfobuthylether-β-cyclodextrin sodium salt) as chiral selector. The influence on the chiral separation of several parameters including pH and concentration of the background electrolyte, chiral selector concentration, applied voltage, system temperature and injection parameters were studied and optimized in order to obtain increased chiral resolution and shorten analysis time. The results were compared with those obtained with native and derivatized neutral cyclodextrins (β-cyclodextrin and hydroxypropryl-β-cyclodextrin). All model molecules were resolved using Captisol® as chiral additive and optimized electrophoretic conditions, proving the efficiency of this anionic derivative of β- cyclodextrin as chiral selector in capillary electrophoresis.